Relevance of Sympathetic Nervous System Activation in Obesity and Metabolic Syndrome - Alicia A. Thorp; Markus P. Schlaich (Journal of Diabetes Research)
Sympathetic tone is well recognised as being implicit in cardiovascular control. It is less readily acknowledged that activation of the sympathetic nervous system is integral in energy homeostasis and can exert profound metabolic effects. Accumulating data from animal and human studies suggest that central sympathetic overactivity plays a pivotal role in the aetiology and complications of several metabolic conditions that can cluster to form the Metabolic Syndrome (MetS). Given the known augmented risk for type 2 diabetes, cardiovascular disease, and premature mortality associated with the MetS understanding the complex pathways underlying the metabolic derangements involved has become a priority. Many factors have been proposed to contribute to increased sympathetic nerve activity in metabolic abnormalities including obesity, impaired baroreflex sensitivity, hyperinsulinemia, and elevated adipokine levels. Furthermore there is mounting evidence to suggest that chronic sympathetic overactivity can potentiate two of the key metabolic alterations of the MetS, central obesity and insulin resistance. This review will discuss the regulatory role of the sympathetic nervous system in metabolic control and the proposed pathophysiology linking sympathetic overactivity to metabolic abnormalities. Pharmacological and device-based approaches that target central sympathetic drive will also be discussed as possible therapeutic options to improve metabolic control in at-risk patient cohorts.